Biomimetic approach to lignin degradation II. The mechanism of oxidative C-C bond cleavage reactions of lignin model compounds with natural iron (III) porphyrin chloride as a hemeenzyme model system - M. Shimada (2018)
Biomimetic oxidation of lignin model compounds such as ß-1, ß-O-4, and ß-5 Substrates was investigated with a natural ironprophyrin which mimicks the ligninase catalysis. 18O from molecular oxygen and water were found to be incorporated, to different degrees, into the C-C bond cleavage product (pmethoxyphenylglycol) formedfrom ß-l Substrate (1,2 bis (pmethoxyphenyl)propane 1,3-diol) under aerobic or anaerobic conditions. Kinetic experiments for catalytic degradation of the ß-1 and its deuterated Substrates supported the one-electron transfer mechanism for the oxygenative C-C bond cleavage previously reported. Other model compounds were also found to undergo C-C bond cleavages in the hemincatalyzed reaction, yielding aromatic aldehydes, ketols and acids. Copyright © 1987 Walter de Gruyter.